Whitening toothpaste containing activated charcoal, blue covarine, hydrogen peroxide or microbeads: which one is the most effective? - Vanessa Torraca Peraro Vaz; Dandara Proba Jubilato; Morgana Regina Mendonça de Oliveira; Janaina Freitas Bortolatto; Michael Christopher Floros; Andrea Abi Rached Dantas; Osmir Batista de Oliveira JUNIOR (University of São Paulo, 2019)
Abstract The efficacy of whitening toothpastes is questionable and controversial. Clinicians, patients and researchers have expressed concern with whitening toothpastes due to the risk of wearing the dental structure and the potential for disappointment if the advertised cosmetic results are not achieved. Objective: This study compared the whitening performance of toothpastes with different whitening technologies after initial and continued use. Material and Methods: Ninety bovine incisors were stained using a concentrated solution of black tea. They were randomly distributed into 6 groups, according to the toothpaste whitening technology: activated charcoal (B&W), blue covarine (WAD), hydrogen peroxide (LWA), microbeads (Oral B 3D White Perfection - 3DW) and optimized abrasives (XW4D). They were compared to a traditional toothpaste without a whitening agent (TA - control). Specimens underwent a brushing machine with controlled pressure, time and temperature. A calibrated examiner measured the color using a VITA-Classical scale before the first brushing cycle (T0), after the first brushing cycle (TI), and after a brushing cycle that simulates continuous use (TCU). Whitening performance was evaluated by the difference of shades (ΔSGU) between T0-TI and T0-TCU timepoints, using the Kruskal-Wallis and Dunn's non-parametric test. The Wilcoxon test was used to evaluate the cumulative effect (α=0.05). Results: Statistically significant differences were observed between toothpastes in both TI and TCU (p<0.05). The time of use also had a significant effect (p<0.05). Conclusion: Only WAD and 3DW showed whitening performance after the first use (TI). The greatest whitening performance after continuous use was obtained by WAD, followed by LWA and 3DW. The use of conventional toothpaste (TA) promotes no tooth whitening. Clinical relevance: Microbead abrasives (3DW) and blue covarine (WAD) were the active technology tested that presented the best global tooth whitening performance.